Advancing Geriatrics Education Through a Faculty Development Program for Geriatrics‐Oriented Clinician Educators. Issue 12 (13th November 2015) - Pinheiro, Sandro O.; White, Heidi K.; Buhr, Gwendolen T.; Elbert‐Avila, Katja; Cohen, Harvey Jay; Heflin, Mitchell T.
Abstract : Geriatrician and nongeriatrician faculty need instruction as teachers to provide quality training for a broader community of physicians who can care for the expanding population of older adults. Educators at Duke University designed a program to equip geriatrician and nongeriatrician faculty to develop quality educational programs and teach medical learners about geriatrics. Eighty‐three faculty representing 52 institutions from across the United States participated in mini‐fellowship programs (2005–09) consisting of workshops and 1‐year follow‐up mentoring by Duke faculty. Participants attended 1‐week on‐campus sessions on curriculum development and teaching skills and designed and implemented a curriculum in their home institution. Participant specialties included general medicine (nearly 50%), family medicine, surgery, psychiatry, rehabilitation medicine, and emergency medicine. Pre‐ and postprogram self‐efficacy surveys, program evaluation surveys, and 6‐ and 12‐month progress reports on scholars' educational projects were used to assess the effect of the Duke mini‐fellowship programs on participants' educational practices. Forty‐four scholars (56%) completed the end‐of‐year self‐efficacy survey and end‐of‐program evaluation. Self‐efficacy results indicated significant gains ( P < .001) in 12 items assessed at 1 week and 1 year. Scholars reported the largest average gains at 1 year in applying adult learning principles in the design of educational programs (1.72), writing measurable learning objectives (1.51), and identifying optimal instructional methods to deliver learning objectives (1.50). Participants described improved knowledge and skills in designing curricula, implemented new and revised geriatrics curricula, and demonstrated commitment to faculty development and improving learning experiences for medical learners. This faculty development program improved participants' self‐efficacy in curriculum design and teaching and enhanced geriatrics education in their home institutions.